2004
DOI: 10.1097/01.tp.0000114283.04840.3a
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus is independently associated with increased insulin resistance after liver transplantation

Abstract: HCV is independently associated with increased IR after OLT. These findings provide a possible pathogenetic basis for the association of DM with HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(73 citation statements)
references
References 35 publications
7
62
1
3
Order By: Relevance
“…Esses dados preliminares sugerem que a infecção pelo VHC serviria como fator de risco adicional para instalação de DM tipo 2 em pessoas com outros fatores de risco estabelecidos para diabetes. Estudos recentes (3,16,20) têm documentado a ocorrência de resistência insulínica em portadores do VHC, mesmo na ausência de doença hepática avançada. A instalação de resistência insulínica poderia ser elo de ligação entre a infecção viral e o desenvolvimento de DM tipo 2 em indivíduos com outros fatores de risco presentes.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Esses dados preliminares sugerem que a infecção pelo VHC serviria como fator de risco adicional para instalação de DM tipo 2 em pessoas com outros fatores de risco estabelecidos para diabetes. Estudos recentes (3,16,20) têm documentado a ocorrência de resistência insulínica em portadores do VHC, mesmo na ausência de doença hepática avançada. A instalação de resistência insulínica poderia ser elo de ligação entre a infecção viral e o desenvolvimento de DM tipo 2 em indivíduos com outros fatores de risco presentes.…”
Section: Discussionunclassified
“…A possível associação entre VHC e DM também é sugerida por estudos transversais que encontraram prevalência aumentada de DM tipo 2 em pacientes com hepatite crônica C, quando comparada à observada em pacientes com outras formas de doença hepática crônica, mesmo na ausência de cirrose (1,2,6,9,11,13) . Embora sua patogênese não esteja defi nitivamente estabelecida, o encontro de índices aumentados de resistência insulínica em pacientes transplantados hepáticos portadores de VHC pode representar a base patogênica da associação VHC e DM tipo 2 (3) . Com o propósito de verifi car esta questão em nossa população, que apresenta perfi l genético e fatores ambientais próprios, desenvolveu-se estudo transversal para determinar a prevalência de infecção pelo VHC em adultos diabéticos.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…However, after transplantation, the mechanism underlying the association between HCV and PTDM is likely to be multifactorial and complex and may be different from those in immunocompetent HCV-positive individuals, owing to concomitant immunosuppression. We have recently found an evidence for increased insulin resistance in HCV-infected liver transplant recipients (23). In another study of kidney transplant recipients, HCV-infected recipients were found to have increased insulin resistance, however, there were no HCV-negative controls for comparison (24).…”
Section: Chronic Hepatitis C Virus (Hcv) Infection Is a Multifaceted mentioning
confidence: 99%
“…37 Infection with HCV has also been associated with an increased risk for insulin resistance and diabetes mellitus in waitlisted candidates and kidney recipients, similar to that reported for the general population. [38][39][40][41][42][43] Although prospective studies are lacking, it is reasonable to assume that the increased incidence of diabetes in the HCV-infected KT candidate/recipient would translate into an increased burden of cardiovascular event risk.…”
Section: Hcv In Patients With Kidney Diseasementioning
confidence: 99%